Enhancing the Cognitive and Learning Skills of Children with Intellectual Disability through Physical Activity and Edutainment Games - Amal Dandashi; Abdel Ghani Karkar; Sawsan Saad; Zaara Barhoumi; Jihad Al-Jaam; Abdulmotaleb El Saddik (International Journal of Distributed Sensor Networks)
This work introduces an edutainment system specifically designed to help children with intellectual disability (ID) in order to allow them to have an enhanced and enjoyable learning process and addresses the need for integrating physical activity into their daily lives. The proposed system consists of a multimedia technology based games with a tangible user interface. The edutainment system was tested on 77 children with different intellectual disabilities (IDs). The mildly disabled groups achieved best results in terms of scores and coordination, but all the observed groups exhibited high motivation levels. The results proved that the system had very positive effects on the children, in terms of cognition and motivational levels, especially as the children became more physically active in the classrooms. Instructors also expressed willingness to incorporate the edutainment system into the classroom on a daily basis, as a complementary tool to conventional learning.